Analisis Perkembangan Usaha Jasa Penjahit di Kecamatan Buleleng - Ni Luh Eva Siwantari; I Nyoman Sujana (Ekuitas: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the development of tailor businesses in Buleleng District and to identify the obstacles faced. The research method used is descriptive qualitative with triangulation techniques through interviews, observation, and documentation involving ten purposively selected tailor business owners. The results indicate that tailor businesses have experienced positive development, as reflected in the increasing number of customers, additional production equipment, and efforts to maintain product quality. Entrepreneurial characteristics such as motivation, creativity, perseverance, and good service are the main factors supporting business growth, although marketing strategies remain conventional. The obstacles encountered include limited capital, minimal financial record-keeping, and low utilization of social media for promotion. The conclusion of this study highlights the need for strengthening managerial capacity, utilizing digital technology, and increasing access to capital in order to support the growth of tailor businesses in Buleleng District.